Diagnóstico del uso de herramientas informáticas básicas en escuelas para niños especiales, en la ciudad de Babahoyo - Estrada Ortiz, Jéssica Lizbeth (2020)
The present work shows a diagnostic study of the use of basic computer tools in schools for special children, in the City of Babahoyo. The tics are an effective means, which, if used in the educational field, can help teachers who work in the early stimulation of special children. The methodology that was carried out in this research is qualitative, the interview instrument was used whose objective was to know if there is a high percentage of use of computer tools in Specialized Institutions, as a result it was obtained that said Institutions are trying to implement computer and internet access; However, there were low indicators in relation to the continuity of use of these computer tools in students with a special disability since they have presented problems in handling them because they did not have specialized hardware and software taking into account that not all disabilities are handled the same.